2022
DOI: 10.3389/fpsyg.2022.1024147
|View full text |Cite
|
Sign up to set email alerts
|

Kolmogorov complexity metrics in assessing L2 proficiency: An information-theoretic approach

Abstract: Based on 774 argumentative writings produced by Chinese English as a foreign language (EFL) learners, this study examined the extent to which Kolmogorov complexity metrics can distinguish the proficiency levels of beginner, lower-intermediate, and upper-intermediate second language (L2) English learners. Kolmogorov complexity metric is a holistic information-theoretic approach, which measures three facets of linguistic complexity, i.e., overall, syntactic, and morphological complexity simultaneously. To assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 60 publications
3
15
0
Order By: Relevance
“…These unique characteristics might make Kolmogorov complexity a suitable measure to examine across and within L2 speaker variation in L2 writing. Despite their strengths, information-theoretic linguistic complexity measures have rarely been utilized in the L2 writing field [ 26 ], e.g., [ 50 , 63 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These unique characteristics might make Kolmogorov complexity a suitable measure to examine across and within L2 speaker variation in L2 writing. Despite their strengths, information-theoretic linguistic complexity measures have rarely been utilized in the L2 writing field [ 26 ], e.g., [ 50 , 63 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…While a sizable number of studies have explored the link between L2 proficiency and non-algorithmic syntactic complexity measures, far fewer studies have investigated this link using Kolmogorov complexity measures [ 26 , 50 ]. A pioneering study by Ehret and Szmrecsanyi [ 50 ] examined the relationship between three Kolmogorov complexity metrics and the amount of L2 instruction using the International Corpus of Learner English (ICLE).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yoon's (2018) study is significant as it points out the potential applicability of morphological diversity in predicting learner proficiency. However, the morphological complexity index (MCI) adopted by Yoon (2018) was later demonstrated to be less predictable in gauging learner proficiency than the Kolmogorov morphological complexity, which exhibited a larger effect size in explaining differences across proficiency levels (Wang, Wang, & Wang, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, Wang, Wang, and Wang (2022) found that Kolmogorov overall and syntactic complexity performed best in distinguishing L2 proficiency, as compared to traditional syntactic and morphological complexity metrics as well as fine‐grained syntactic complexity metrics. This positions the Kolmogorov complexity as a robust tool, capable of predicting learner proficiency through its three layers: overall, morphological, and syntactic.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation